Desain Inti (Core) Reaktor SCWR (Super Critical Water-cooled Reactor) Tiga Dimensi (X-Y-Z) Menggunakan Bahan Bakar Thorium Hasil Daur Ulang - Sri Harjanti; Yanti Yulianti; Pulung Karo Karo (Department of Physics, Faculty of Mathematics and Natural Sciences, University of Lampung, 2017)
The research of three-dimensional (X-Y-Z) core design of SCWR reactor using thorium recycled has been done. Neutronic calculations were calculated by SRAC program. Parameters of this research werefuel enrichment, core reactor sizes, core reactorconfigurations, criticality, and power density distribution. The desain of core reactor was 1/8 three-dimensional (X-Y-Z) slab. Fuel reactor was thorium 20 GWd/t burn as inner,and 30 GWd/t burn as outer. Zirconium as cladding,and light water as coolant. Critical condition was achieved at x = 310 cm, y = 170 cm, z = 190 cm and 2,49% of fuel enrichment. Core power reactor was 3.411 MWt, maximum power density was 366,8356 Watt/cc located at x = 34 (170 cm), y = 1 (5 cm), z = 38 (190 cm) and multiplication factor effective (keff) value was 1.0000000.